xamining the relationship between professional identity and psychological well-being among nurses - Fahima Hayarati; Fatemeh Taheri; Maliheh Abdullahi; Naheed Reyhani (Zanjan University of Medical Sciences and Health Services, 2024)
Background: Various factors are known to influence psychological well-being and professional identity, both of which can subsequently affect the optimal performance and efficiency of nurses. Objectives: The present study was conducted to investigate the relationship between professional identity and psychological well-being among nurses. Methods: The current research was a descriptive correlational study conducted on 242 nurses in 2021. The hospitals of Birjand City were selected by cluster sampling based on the inclusion criteria. The data were collected using a demographic information questionnaire, the Ryff psychological well-being questionnaire, and Hao's professional identity questionnaire. Data were analyzed by SPSS 19 software using the independent t-test, one-way analysis of variance, chi-square, Pearson correlation, and Spearman correlation. Results: The results showed that the mean (SD) score of professional identity in nurses was 58.49 (10.09), and the average score (SD) of psychological well-being among the nurses was 69.74 (10.96). There was a positive and significant relationship between psychological well-being and professional identity, meaning that with the improvement of professional identity, the level of psychological well-being also increased among nurses (sig=0.005, α=0.185). Conclusion: By promoting professional identity, it is possible to upgrade psychological well-being among nurses. This can be achieved by implementing stress-coping measures such as optimization of the work conditions and work indicators, which can promote nurses' professional identity and, subsequently, psychological well-being.